Comorbid Depression and Substance Abuse in Perpetrators of Domestic Homicide - Oliver, Casey (2018)
Globally up to 38% of murdered women are victims of domestic homicide. However, research has yet to examine comorbid depression and substance abuse in domestic homicide, despite comorbid mental health conditions being associated with homicide in the general population. A retrospective case analysis approach was performed using domestic homicide cases that had been reviewed by the Domestic Violence Death Review Committee of Ontario. Group comparisons were made by compiling cases into groups based on perpetrator mental health status: a no mental illness group, depression only group, substance abuse only group, and comorbid depression and substance abuse group. Statistical analyses compared groups on number and types of risk factors and service provider contacts, as well as on other variables of interest. Results indicated unique patterns of risk factors and service provider contacts for each group of perpetrators. Recommendations for service providers who connect with perpetrators of domestic violence are discussed